Predicting the Phenology of Herbivorous Insects - Zimo Yang; Elise Woodruff; David Held; Nate B. Hardy (Ecology and Evolution, 2025)
ABSTRACT Models of herbivorous insect phenology can be used to make agriculture more sustainable and to better manage the effects of climate change on natural communities. The phenology of herbivorous insects depends on heat time, but exactly how it varies across populations and the causes of this variation are unclear. Here, with multilevel Bayesian models, we performed a comparative analysis of 601 published herbivorous insect phenology models. We found that variation in herbivorous insect phenology can be explained by variation in phylogenetic relatedness, adult body size, feeding site, host plant taxonomy, geographic location, and the approaches that researchers used for model parameterization. Contrary to previous analysis, we also found that the minimum temperature required for development varies across life stages in a way that could be adaptive. Our analysis demonstrates that by accounting for more information on the variation across insect populations and their environments, we can make better and more generalizable predictions of herbivorous insect phenology.